Stress Fracture of the Os Metatarsale I in a Swimmer - Van Caspel, J.; Heere, L.P. (Biomechanics and Medicine in Swimming, 1983)
Breithaupt (1855) first presented a clinical description of a stress fracture without fully understanding its exact etiology; Stechow (1897) was the flrst to establish its radiological aspects. In those years such fractures were mainly seen in army recruits, ea. 80o/o of the cases being localized in the metatarsal bones, usually the os metatarsale Ill (Doury et al., 1979). This type of fracture has also been referred to as a "march fracture" or a "fatigue fracture." Recently stress fractures have been described in various sites of the lower extremities in athletes, especially runners (Taunton et al., 1981). The following case deals with a swimmer's stress fracture suffered in the course of an intensive training program in which extra large fins were used. Research of the literature has not revealed any previous presentations of cases with a similar etiology. This type of fracture, moreover, is seldom seen in this particular locus (MT 1).